An assessment of the attitudes of undergraduate students towards information literacy training : Sefako Makgatho Health Sciences University (SMU) Library as case study - Fourie, Ina (University of Pretoria, 2017)
Mini Dissertation (MIT)--University of Pretoria, 2016.